2006
DOI: 10.1111/j.1747-7093.2006.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration, Multiculturalism, and the Welfare State

Abstract: Popular opposition to immigration is rooted in many factors. In this essay, we focus on one specific issue that has become prominent in recent debates—namely, the fear that the welfare state is being undermined by the impact of increasing ethnic and racial diversity. There are actually two concerns here: first, that ethnic and racial diversity as such makes it more difficult to sustain redistributive social policies because it is difficult to generate feelings of national solidarity and trust across ethnic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 0 publications
1
89
0
10
Order By: Relevance
“…For example, Ukrainians, Italians, and other European immigrants led the multiculturalism discussions and debates in the 1960s and 1970s. Kymlicka argues that multiculturalism in Canada was not initially intended to accommodate Canadian Muslims, or to enhance their positive integration into the wider Canadian society It can be argued that when multiculturalism was introduced it was a reasonable response to already established communities of immigrants, but lacked flexibility in accommodating the needs of new immigrants, and did not consider, let alone address, the challenges faced by Muslims and similar minorities in their struggle to survive (Kymlicka, 2006).…”
Section: Multiculturalismmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ukrainians, Italians, and other European immigrants led the multiculturalism discussions and debates in the 1960s and 1970s. Kymlicka argues that multiculturalism in Canada was not initially intended to accommodate Canadian Muslims, or to enhance their positive integration into the wider Canadian society It can be argued that when multiculturalism was introduced it was a reasonable response to already established communities of immigrants, but lacked flexibility in accommodating the needs of new immigrants, and did not consider, let alone address, the challenges faced by Muslims and similar minorities in their struggle to survive (Kymlicka, 2006).…”
Section: Multiculturalismmentioning
confidence: 99%
“…The commission concluded that there was Canadian complicity in Arar's imprisonment and torture, and offered an official apology and financial compensation.. According to Kymlicka (2006), multiculturalism in Canada was originally established for the benefit of well-integrated European ethnic groups who had only minor differences in terms of culture and language with the dominant group. For example, Ukrainians, Italians, and other European immigrants led the multiculturalism discussions and debates in the 1960s and 1970s.…”
Section: Multiculturalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweden has been, by far the most permissive whereas Finland and Norway, and especially Denmark, are more regulated. Taking more types of policies into account, including the allowance of dual citizen-ships and the funding of ethnic group organizations or activities, Kymlicka and Banting (2006) classify 21 OECD countries according to their multiculturalism. Sweden is the only Nordic country having modest multiculturalism policies, whereas Denmark, Finland and Norway are categorized as having weak multiculturalism policies.…”
Section: The Nordic Countries: Moving Towards More Heterogeneitymentioning
confidence: 99%
“…Although the crisis has clearly not supported the maintenance of a strong, redistributive, and egalitarian welfare state overseeing and guarding social cohesion, it should be acknowledged that even without the crisis, the welfare state (which exists in many guises, and in some regions of the world not at all) is facing serious difficulties, partly due to additional economic pressures (mainly deriving from soaring costs of social benefits, education, and health care), partly the erosion of national sovereignties, and partly the liberalization and transnationalization of economic flows, which erode the taxation basis of states [13]. This in turn implicates the third factor, generic global shift and flows, involving both a multipolar restructuring of global politics and massive demographic cross-border mobility-developments which challenge receiving societies (already weakened due to crisis effects and overtaxed welfare systems) to devise intelligent instruments and models for coping with novel and ever fluctuating diversity [14][15][16].…”
mentioning
confidence: 99%